2019
DOI: 10.23971/jefl.v9i1.961
|View full text |Cite
|
Sign up to set email alerts
|

Promoting mobile collaborative language learning in Islamic higher education

Abstract: <span lang="EN-US">This study sought to explore students’ experience in using Instagram to participate in mobile collaborative language learning (MCLL)</span><span lang="EN-US">. T</span><span lang="EN-US">he</span><span lang="EN-US"> contents they </span><span lang="EN-US">produced and shared, a</span><span lang="EN-US">s well as</span><span lang="EN-US"> their interaction and collaboratio</span><span lang="EN-US">n, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…Practicing writing through blogging provided the students with the chance to improve their writing abilities and focus on the content. Another research by Yudhiantara and Nuryantini (2019) found that the use of Instagram enhanced the students' interaction through peer feedback. The study confirmed that giving and receiving feedback from their peers could improve their writing and translating skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practicing writing through blogging provided the students with the chance to improve their writing abilities and focus on the content. Another research by Yudhiantara and Nuryantini (2019) found that the use of Instagram enhanced the students' interaction through peer feedback. The study confirmed that giving and receiving feedback from their peers could improve their writing and translating skills.…”
Section: Discussionmentioning
confidence: 99%
“…A survey study by Li (2017) showed that social media, for instance, YouTube, Blogs, Forums, and Wikis have been widely used in teaching English either as sources of learning, media of instruction and communication, or as informal learning tools. In the same vein, research by Yudhiantara and Nuryantini (2019) showed that using Instagram helped improve the students' skills in translating and writing sentences as they practiced giving feedback to others' drafts. In conclusion, social media application can be utilized as teaching and learning tools because their features allow for continuous connection and communication.…”
mentioning
confidence: 98%
“…It is showed that the surge of interest in any kind of MobApps has taken a place in the EFL teaching and learning modes [1] [2]. Therefore, the use of MobApps gives great changes in English education in terms of the cognition of teachers and students, instructional materials design, the role of students and teachers in practice, and evaluation and testing [3].…”
Section: Introductionmentioning
confidence: 99%
“…Social media applications, such as Instagram and WhatsApp, can be designed to support the process of learning English (Yudhiantara & Nuryantini, 2019a). Instagram can be directed to improve students' ability to collaborate to learn English (Yudhiantara & Nuryantini, 2019b). Education in the 21st century needs to equip students with the ability to learn using online technology and also hone students' collaboration skills.…”
Section: Cognitive Presence Elementmentioning
confidence: 99%
“…To collaborate, there are many social media applications, such as Instagram and the like, that can be designed to support the process of learning English (Yudhiantara & Nuryantini, 2019a). In addition to this, Instagram can be directed to improve students' ability to collaborate in learning English (Yudhiantara & Nuryantini, 2019b).…”
Section: Introductionmentioning
confidence: 99%